2013
DOI: 10.1371/journal.pone.0077731
|View full text |Cite
|
Sign up to set email alerts
|

Massively Parallel Sequencing Reveals an Accumulation of De Novo Mutations and an Activating Mutation of LPAR1 in a Patient with Metastatic Neuroblastoma

Abstract: Neuroblastoma is one of the most genomically heterogeneous childhood malignances studied to date, and the molecular events that occur during the course of the disease are not fully understood. Genomic studies in neuroblastoma have showed only a few recurrent mutations and a low somatic mutation burden. However, none of these studies has examined the mutations arising during the course of disease, nor have they systemically examined the expression of mutant genes. Here we performed genomic analyses on tumors ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 65 publications
2
16
0
Order By: Relevance
“…1). We and others have reported the same phenomenon that approximately 50% of DNA somatic mutations are expressed in the RNA (22, 23). …”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…1). We and others have reported the same phenomenon that approximately 50% of DNA somatic mutations are expressed in the RNA (22, 23). …”
Section: Resultssupporting
confidence: 57%
“…Our WTS results showed that about one-half of all SNVs are not expressed in the transcriptome, and thus can be excluded as a driver mutation. We and others have reported the same phenomenon that approximately 50% of DNA mutations are expressed in the RNA (22, 23). The cause is usually that the RNA transcript, and hence, the gene, is not expressed at the RNA level.…”
Section: Discussionsupporting
confidence: 61%
“…Total RNA was extracted, RNA-seq libraries were made and sequenced as previously described [55, 56]. The integrity of total RNA was evaluated using an Agilent BioAnalyzer 2100 (Agilent, Palo Alto, CA), and only RNAs with RIN greater than 6.0 were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is clear from early studies that clonal evolution is common in neuroblastoma and that relapsed neuroblastoma tumors acquire many additional segmental chromosomal alterations that may have prognostic implications in the relapsed setting . More recent focused studies using genomic deep‐sequencing efforts have suggested that clonal evolution also results in the acquisition of targetable somatic aberrations in known oncogenic pathways, and early evidence suggests that these converge on the mitogen‐activated protein (MAP) kinase (MAPK) pathway . Although the MAPK pathway is a key driver of oncogenicity in several human malignancies, until recently, this was not believed to be the case in neuroblastoma, because MAPK pathway mutations are rare in primary neuroblastoma tumors (although NRAS was discovered in neuroblastoma) .…”
Section: Clonal Evolution: Current Understanding and Druggable Opportmentioning
confidence: 99%
“…68 More recent focused studies using genomic deep-sequencing efforts have suggested that clonal evolution also results in the acquisition of targetable somatic aberrations in known oncogenic pathways, and early evidence suggests that these converge on the mitogen-activated protein (MAP) kinase (MAPK) pathway. 88,89,106,107 Although the MAPK pathway is a key driver of oncogenicity in several human malignancies, until recently, this was not believed to be the case in neuroblastoma, because MAPK pathway mutations are rare in primary neuroblastoma tumors (although NRAS was discovered in neuroblastoma). 40,108 However, in a recent, comprehensive, deep-resequencing study of 23 relapsed/ refractory neuroblastomas, 78% of relapsed specimens ALK Mutation/focal amplification c 8%-14% (Sausen 2013, 39 Pugh 2013, 40 Molenaar 2012, 41 Cheung 2012, 42 Shukla 2012 87 ) 26%-43% (Schleiermacher 2014, 88 Eleveld 2015 89 ) c ALK mutation/amplification ALK inhibition (Barone 2013, 35 Carpenter & Mosse 2012 91 Gogolin 2013 92 ) CDK4/6 inhibition (Rader 2013, 91 Gogolin 2013 91 Gogolin 2013 92 ) CDK4/6 inhibition (Rader 2013, 91 Gogolin 2013 ) 13%-22% (Eleveld 2015, 89 Carr-Wilkinson 2010 94 ) MYCN amplification (Rader 2013, 91 Gogolin 2013 92 ) CDK4/6 inhibition (Rader 2013, 91 Gogolin 2013 96 Gamble 2012, 97 Van Maerken…”
Section: Clonal Evolution: Current Understanding and Druggable Opportmentioning
confidence: 99%